The Application of the Studio Learning Method in Improving the Learning Quality of Interior Design I - Dwi R.S. Ambarwati (JOURNAL OF EDUCATION, 2012)
This study is aimed at improving the learning quality of Interior Design I in the Visual Arts Education Department, Faculty of Languages and Arts, Yogyakarta State University. The method  conducted  in  this study was classroom action research following  the four  steps: (1) preparing action plans, (2) implementing the action plan, (3) observing the action, and (4) reflecting. This research was conducted in 2 cycles. The results show  that  the studio learning method has proven to enhance students'  learning achievement in three aspects of cognitive, affective and psychomotor in terms of 1) consistency and suitability in function, dimensions, standardization, security considerations and comfort,  the selection  of shapes, styles, materials and colors, suitability in determining space conditions (80%); 2) originality in doing individual task (80%); 3) sensitivity in design composition (80%); 4)  creativity in producing new designs (80%); 5) accuracy in technical drawing (80%); and  6)  time accuracy in task submission (100%). In conclusion, the aplications of the studio learning method can improve learning quality.   Keywords: studio learning method, interior design